Sociological Explanation of the Fair Distribution of Resources and Wealth in the Perspective of the Qurʾān - Seyyed Mohsen Mirsondosi (آموزه‌های قرآنی)
The intellectual systems designed for the leadership of humankind and the construction of both the individual and society each propose specific plans and programs tailored to their societal and social contexts. A fundamental component of these systems is the method of distributing valuable resources within the society in question. This paper, with the objective of providing a sociological examination of the fair distribution of resources and wealth from the perspective of the Qurʾān, primarily addresses the question of what factors and obstacles can be inferred from the Qurʾānic verses concerning the fair distribution of resources and their impact on social justice. Furthermore, from a sociological standpoint, how these factors contribute to the realization of social justice and the ideal society envisioned in the Qurʾān is analyzed. The research methodology of this study is qualitative analysis, discovering themes related to the issue based on a framework of sociological concepts and direct reference to the Qurʾānic verses. The findings of the research present a model of positive and negative factors, identified as both the foundations and barriers for fair distribution. The positive factors include the promotion of a culture of charity (Arabic: صدقة, Romanized: ṣadaqah), trust-building in economic exchanges, attention to the belief in God as the provider (Arabic: رزاق, Romanized: razāq), and the payment of zakat (Arabic: زکات), all of which are recognized as key enablers of fair wealth distribution. Conversely, negative factors such as the promotion of unhealthy lifestyles, neglect of the needs of the underprivileged, the unequal accumulation of wealth, and wastefulness (Arabic: إسراف, Romanized: isrāf) were highlighted as significant obstacles to achieving social justice. The results demonstrate that Qurʾānic teachings clearly emphasize the importance of cooperation and mutual assistance within society, providing the necessary foundation for establishing a just and sustainable system.